ANALYSIS OF LAND COVER CHANGE IN MOROWALI USING LANDSAT 8 SATELLITE IMAGERY AND UNSUPERVISED CLASSIFICATION METHOD - Benedictus Lanang Ido Hernanto; Hendry, Hendry (Bajang Institute, 2025)
Land use changes reflect the ecological and socio-economic dynamics of a region. This study aims to analyze land cover changes using Landsat 8 satellite imagery with the unsupervised classification method. Land cover is categorized into five classes: light vegetation, dense vegetation, rice fields, plantations, and settlements and mining areas. The analysis was conducted by comparing data from 2013 and 2018. The results indicate a significant increase in the area of mining and settlements by 71.60 km² and 476.88 km², respectively. Conversely, the area of rice fields and light vegetation decreased by 1117.93 km², natural canopy decreased by 672.03 km², and plantations decreased by 524.84 km². These findings indicate land conversion from natural vegetation to non-vegetative areas due to mining industry expansion and settlement growth. This study provides valuable insights for more sustainable land-use planning in the future